SAT-387 Hypothalamic-Pituitary-Adrenal Axis in Elderly Women with Memory Impairment - Arregger, Alejandro (J Endocr Soc, 2019)
Daily stress and aging have been associated with detrimental effects on memory. However, the role of lifestyle on the HPA axis regulation remains unclear.The aim of this study was to evaluate the relationship between lifestyle, memory and the HPA axis feedback regulation in aging women. Seventy women aged 65-87 y/o who complained of poor memory were interviewed, 30 of them met the inclusion criteria (absence of dementia, stroke, general anesthesia during the last year, endogenous depression, renal and hepatic insufficiency, drug or alcohol abuse and any medication that may affect the HPA axis). Only 28 completed the study. They obtained whole saliva samples to evaluate the daily rhythm of salivary cortisol (SAF) at 8.00 (SAF(8)), 16.00(SAF(16)) and 23.00 H (SAF(23)). The sensitivity of the HPA axis was assessed by the overnight 0.5 mg dexamethasone suppression test (DST). SAF and salivary dexamethasone (saD) after DST were determined at 8.00 (SAF(8dex),saD(8)) and at 16.00 (SAF(16dex),saD(16)). Reference values from our laboratory are: SAF(8) ≤ 18.0 nM, SAF(16) ≤ 6.0 nM, SAF(23) ≤ 3.8 nM; SAF(8dex) and SAF(16dex)≤2.0nM, saD≥0.229 nM. Lifestyle (LS) and quality of life (QL) were evaluated by self-administered questionnaires (LS and SF36, respectively). Episodic, working and semantic memories, visuospatial perception and attention were also assessed. The protocol was approved by the Ethics Committee of IDIM A. Lanari and all subjects gave their written informed consent. SAF and saD were determined by RIA and ELISA, respectively. Statistics were performed by SPSS (p <0.05 was considered significant). Three patients did not suppress salivary cortisol (Sup-) at 8.00 and 16.00 H (SAF(8dex): 10.6 ± 6.8nM and SAF(16dex): 4.2±1.3nM); while 25 suppressed normally (Sup+). saD was not different between both groups. All subjects kept normal SAF diurnal variation although the slope was significantly less steep in Sup-(p<0.0001). Lifestyle index was significantly lower in Sup- than in Sup+, p=0.02, while there were no differences in QL. Thirteen out of 28 patients showed mild cognitive impairment (MCI). Among the MCI patients only the Sup- group had inadequate performance in 4 sections of the Rey Auditory Verbal Learning Test. Brain RMN performed in 2 Sup- showed enlargement of the sphenoidal extension of the lateral left ventricle that could be related to shrinkage of the ipsilateral medial temporal lobe. These findings suggest that DST might become a non-invasive approach to detect hippocampal damage in aging women with MCI.